P16.11 Vitamin C levels and the hypoxic pathway in human glioma tissues. (9th September 2021) - Burgess, E R; Crake, R L I; Phillips, E; Morrin, H R; Royds, J A; Vissers, M C M; Robinson, B A; Dachs, G U
Abstract: BACKGROUND: Gliomas are the most common brain cancer and survival is poor, with 11–15 months for high-grade glioblastoma patients, despite treatment. Gliomas are hypoxic tumours, which increases with tumour grade. Under hypoxia, the transcription factor hypoxia inducible factor-1 (HIF) accumulates and upregulates expression of genes involved in tumour development and progression. HIF-1 levels and activity are controlled by HIF hydroxylases which target HIF-1α for degradation and prevent co-activation. HIF hydroxylases are part of the 2-oxoglutarate (2-OG)-dependent dioxygenase enzyme family, that require 2-OG and oxygen as substrates and ascorbate and iron as co-factors. The role of ascorbate in regulating the hypoxic pathway in cancer is of interest, with previous research showing reduced HIF pathway activity with increasing tumour ascorbate levels. Brain tissue has one of the highest ascorbate levels in the body, and is one of the last to become depleted under deficiency, indicating an important role for ascorbate in this tissue. One previous study has analysed ascorbate levels in 11 human glioblastoma patients, and showed lower ascorbate in tumour tissue compared to normal brain tissue. There have been no studies investigating the relationship between ascorbate levels and the hypoxic pathway in human glioma tissues. MATERIAL AND METHODS: Human glioma tissues (n = 39), obtained from the Cancer Society Tissue Bank Christchurch (ethics approval H19/163), were processed for ascorbate and hypoxic pathway proteins (HIF-1α, CA-IX, BNIP3, HKII, GLUT1 and VEGF). Ascorbate levels were quantified by HPLC-ED, and proteins were measured by Western blotting and ELISA. Spearman's correlations were used to identify relationships between ascorbate and HIF pathway proteins. RESULTS: Of the samples, 64% were GBM. Ascorbate was significantly lower in GBM compared to low-grade gliomas (p = 0.04). VEGF was significantly higher in GBM compared to astrocytomas (p = 0.01). Increased tumour ascorbate was associated with lower VEGF and CA-IX proteins. HIF-1α and BNIP3 protein were positively associated, and VEGF was positively associated with HKII and CA-IX. VEGF inversely associated with BNIP3, and CA-IX inversely associated with HKII. The hypoxic pathway score (calculated from protein levels of members of the hypoxic pathway) was reduced in tumours with higher ascorbate but this did not reach significance (p = 0.2). CONCLUSION: This is the first study to show that ascorbate levels were reduced in high-grade gliomas compared to low-grade. Some members of the hypoxic pathway were associated with ascorbate levels. The overall hypoxic pathway score did not significantly correlate with ascorbate and increased numbers of samples are required to confirm any associations. Other variables, such as IDH-1 mutation status of the tumours may affect the correlation and will be analysed next.